STATUS HUKUM TERTIB DALAM RUKUN DUA KHUTBAH JUM’AT (TELAAH KRITIS FIQIH KLASIK) - Multazim A. A. (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2019)
Shalat jum’at is a decree of Allah and His apostles to do all Muslims who ain yaikni fardlu legal status must be done by each community male, adult, independent and living in an area (habitation), there shall be a Muslim, children children, slaves and people who are traveling (Musafir). Friday prayer is done in a certain way and only considered valid if it qualifies and harmony. One of the requirements unauthorized Shalat jum’at among others should be preceded two Friday sermons. Two sermons can also be considered valid if it qualifies and harmony. The two pillars of the popular sermons in practice in the community is reading hamdalah, and prayers be upon our Prophet Muhammad, intestate piety to Allah SWT, read one verse on one of the two sermons, and pray for the Muslims and muslimat the second sermon. The five things orderly recitation even any dillakukan orderly implementation, though, none of the verses of the Koran or al-Hadith that explains directly that the implementation of the pillars of the two sermons should be conducted in an orderly. That's why there needs to be a positive answer and more maslahah create the legal status orderly people in the pillars of two sermons.